Case Report: High doses of Zolpidem and QT interval lengthening: Is there a relationship? A case series - Campagnari, Simone; Zamboni, Lorenzo; Fusina, Francesca; Casari, Rebecca; Lugoboni, Fabio (Frontiers in Psychiatry, 2022)
Zolpidem is indicated in cases of severe insomnia in adults and, as for BDZs, its assumption should be limited to short periods under close medical supervision. Since several drugs cause corrected QT interval (QTc) elongation, the authors investigated whether high daily doses of Zolpidem could cause QTc elongation. The study was conducted in the Addiction Medicine Unit of the G.B. Rossi University Hospital in Verona. The data were collected from hospitalizations carried out between January 2015 and February 2020 and refer to a total of 74 patients, 38 males and 36 females, who were treated for detoxification from high doses of Zolpidem with the “Verona Detox Approach With Flumazenil”. One patient out of 74 had QTc elongation (479ms). The patient was a male and took a daily dose of 50 mg of Zolpidem; he did not take concomitant therapies that could cause QTc lengthening, he had no electrolyte alterations, no contemporary or previous intake of barbiturates, heroin, cocaine, THC, alcohol, NMDA or nicotine which could cause an elongation of the QTc interval. The present study highlights the low risk of QTc elongation due to high dosages of Zolpidem; however, if on the one hand we can affirm that Zolpidem is a safe drug, on the other, the widespread use of high dosages and for prolonged periods is problematic and worrying.